The Perspective of the Acehnese Community in Indonesia toward HIV/AIDS - Alvis Syahru Ramadhan; Laili Rahayuwati; Ahmad Yamin; Vira Amelia (Jurnal Promosi Kesehatan Indonesia, 2025)
Background: HIV/AIDS has garnered public attention due to the challenges in its effective control, with its prevalence continuing to rise until 2019. Despite its global impact, public awareness of this disease remains limited. The perspective of the community on People Living with HIV/AIDS (PLWHA) in the Aceh region offers unique insights, indicating existing issues in the community environment. However, a comprehensive understanding of these issues is still lacking. This study aims to explore the challenges related to the Acehnese people's perspective towards PLWHA.Method: A qualitative ethnographic design was employed, focusing on the subjective approach to understanding the perspectives of the Acehnese Community. In-depth interviews were conducted with 8 participants. The researcher served as a human instrument, directly involved in collecting and interpreting the data. Data were analyzed descriptively using iterative coding and thematic categorization.Result: The study identified three themes related to the perspective of the community on People Living with HIV/AIDS (PLWHA): (1) Community Knowledge regarding HIV/AIDS and PLWHA, (2) Experiences of the Acehnese Community with HIV/AIDS and PLWHA and (3) Community Values towards HIV/AIDS and PLWHA. Individuals with knowledge about HIV/AIDS can provide proper care for PLWHA patients, fostering an understanding of transmission dynamics. Society exhibits positive attitudes towards PLWHA when exposed to sufficient information. Conversely, negative perceptions arise when society attributes the disease to certain behaviors or considers it as a curse, leading to non-acceptance and ostracism. The perspectives imposed on PLWHA significantly influence their perception of the surrounding community. Community knowledge is crucial in shaping these perspectives, particularly from individuals with experience caring for PLWHA. Society holds both positive and negative values concerning HIV/AIDS and PLWHA.